PEMBUATAN APLIKASI PEMBELAJARAN PENCARIAN AKAR PERSAMAAN - Amanda A. Diadema; Gunawan Santosa; Nugroho Agus Haryono (Jurnal Informatika, 2013)
In numerical methods, finding the root of an equation involves iterations to find an estimated root approximating the original root. Several methods that can be used to find the root are Fixed-Point Iteration Method, Newton-Raphson Method, Secant Method and the Muller Method. This learning software is developed to provide a learning media for students to learn how to find the root of an equation. It contains animated explanation of the study material, case study and exercises. The software then tested to users using Usability Test, namely compatibility, consistency, flexibility, learnability, perceptual limitation, and minimal action. Tests performed to undergraduate students who have learned how to find equation root yield these results: Compatibility 86.13%, Consistency 83.73%, Flexibility 84.23%, Learnability 81.87%, Minimal Action 84.80%, and Perceptual Limitation 85.07%. On the other hand, tests performed to undergraduate students who have never learned how to find equation root yield these results: Compatibility 85.33%, Consistency 86.67%, Flexibility 83.47%, Learnability 85.87%, Minimal Action 87.20%, and Perceptual Limitation 82.67%.